2016
DOI: 10.4137/cmed.s39035
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus, a New Risk Factor for Lumbar Spinal Stenosis: A Case–Control Study

Abstract: OBJECTIVESThis study aimed to determine the prevalence of diabetes mellitus in patients with spinal stenosis and lumbar vertebral disk degeneration, and the correlation of diabetes with these diseases.STUDY DESIGNThis is a cross-sectional study.METHODSThis case–control study was performed during 2012–2014 with 110 patients suffering from lumbar spinal stenosis and 110 patients with lumbar disk herniation, who were diagnosed using clinical and radiological evidences. Additionally, 110 participants who were refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 11 publications
(18 reference statements)
0
41
0
1
Order By: Relevance
“…(2,3). Diabetes mellitus is considered a risk factor for the development of lumbar spinal stenosis (4,5). Numerous studies have shown that vertebral body and accessory lesions, including osteoporosis (6), compression fractures of lumbar vertebrae (7), benign and malignant tumors (8,9), and hematologic disease (10), are closely related to the permeability of bone marrow and vertebral fat deposition.…”
Section: Author Contributionsmentioning
confidence: 99%
“…(2,3). Diabetes mellitus is considered a risk factor for the development of lumbar spinal stenosis (4,5). Numerous studies have shown that vertebral body and accessory lesions, including osteoporosis (6), compression fractures of lumbar vertebrae (7), benign and malignant tumors (8,9), and hematologic disease (10), are closely related to the permeability of bone marrow and vertebral fat deposition.…”
Section: Author Contributionsmentioning
confidence: 99%
“…The prevalence of lifestyle diseases, such as hypertension, DM, and PAD, has been reported to be high among individuals with LSS [ 6 , 8 , 26 , 27 ]. The prevalence of DM is particularly high (13.6–29.1%) and has been considered a risk factor for LSS.…”
Section: Discussionmentioning
confidence: 99%
“…However, many healthy individuals also demonstrate similar age-related changes, including similar degrees of radiographic LSS (rLSS) to that in patients with sLSS, but remain asymptomatic [ 5 ]. Recent studies have shown that lifestyle-related diseases such as diabetes mellitus (DM), peripheral artery disease (PAD), and heart disease, are frequently associated with sLSS [ 6 8 ]. However, the prevalence of medical comorbidities also increases with age, and to our knowledge, most previous studies were case-control studies with selection bias.…”
Section: Introductionmentioning
confidence: 99%
“…The exclusion criteria were as follows: (i) prior spine surgery; (ii) systemic inflam-matory disease; (iii) neurologic disorder; (iv) acute trauma, neoplasm, or infection; (v) spinal deformities or spondylolisthesis (over Meyerding grade II); and (vi) diabetes. The rationale for the exclusion of patients with diabetes was the association between LF thickness and diabetes reported in previous studies 10,11) . The equipment comprised a spine coil with a GE Signa HDx 1.5 T (GE Healthcare, Milwaukee, WI, USA).…”
Section: Methodsmentioning
confidence: 99%